Genotyping of fusarium isolates from onychomycoses in Colombia: detection of two new species within the fusarium solani species complex and in vitro antifungal susceptibility testing (2020)
Fusariosis have been increasing in Colombia in recent years, but its epidemiology is poorly known. We have morphologically and molecularly characterized 89 isolates of Fusarium obtained between 2010 and 2012 in the cities of Bogotá and Medellín. Using a multi-locus sequence analysis of rDNA internal transcribed spacer, a fragment of the translation elongation factor 1-alpha (Tef-1α) and of the RNA-dependent polymerase subunit II (Rpb2) genes, we identified the phylogenetic species and circulating haplotypes. Since most of the isolates studied were from onychomycoses (nearly 90 %), we carried out an epidemiological study to determine the risk factors associated with such infections. Five phylogenetic species of the Fusarium solani species complex (FSSC), i.e., F. falciforme, F. keratoplasticum, F. lichenicola, F. petroliphilum, and FSSC 6 as well as two of the Fusarium oxysporum species complex (FOSC), i.e., FOSC 3 and FOSC 4, were identified. The most prevalent species were FOSC 3 (38.2 %) followed by F. keratoplasticum (33.7 %). In addition, our isolates were distributed into 23 haplotypes (14 into FOSC and nine into FSSC). Two of the FSSC phylogenetic species and two haplotypes of FSSC were not described before. Our results demonstrate that recipients of pedicure treatments have a lower probability of acquiring onychomycosis than those not receiving such treatments. The antifungal susceptibility of all the isolates to five clinically available agents showed that amphotericin B was the most active drug, while the azoles exhibited lower in vitro activity